ANALISIS USER EXPERIENCE APLIKASI E-KINERJA DI DINAS KOMUNIKASI DAN INFORMASI MUARA ENIM MENGGUNAKAN METODE USER EXPERIENCE QUESIONNAIRE - Anggita, Maya; Supratman, Edi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to evaluate the user experience of the e-Kinerja application used in the Muara Enim Regency Communicat ion and Information Agency. The method used is the User Experience Questionnaire (UEQ), which measures six main dimensions of user experience, namely attractiveness, efficiency, clarity, accuracy, stimu lation, and novelty. The results show that the e-Kinerja application provides a positive experience for users. The application is consi dered easy to use, clear in presenting information, and capable of encouraging work productivity. There are several aspects that can be improved to support innovation and accuracy of the application's functions. The evaluation is expected to be the basis for developing a more effective application that is oriented towards user needs. The research results are expected to contribute to improving the quality of information technology-based services in the govern ent sector and serve as a reference for other agencies in developing similar applica tions. Thus, this research not only assesses the current performance of the e-Kinerja application but also encourages the creation of adaptive, innovative systems that are in line with the evolving needs of organizations and society.